Knock out aryl hydrocarbon receptor gene in adipose-derived mesenchymal stem cell line (PT-5006) by CRISPR/Cas9 - Duc, Le Hoang; Tien, Vu Thi; Nam, Nguyen Trung (Vietnam Journal of Biotechnology, 2024)
Mesenchymal stem cells (MSCs) have garnered significant attention in biomedical studies due to their remarkable properties, such as self-renewal, differentiation into diverse cell types and immune responses. The proliferation and differentiation of MSCs are significantly influenced by the ligand-dependent transcription factor known as the aryl hydrocarbon receptor (AhR). In order to understand the roles of Ahr in adipose-derived MSCs (AD-MSCs), we disrupted the Ahr gene in this work using CRISPR/Cas9 gene editing technology. The gRNA/Cas9 dual vector and donor vector were introduced into the AD-MSC cell line (PT-5006). Green fluorescent protein (GFP) expression and puromycin resistance were used to identify the transfected cells. AhR-KO cells were cloned and confirmed by PCR and sequencing. By using RT-qPCR, the expression levels of AhR and the Ahr-related gene Cyp1B1 were investigated. The results showed that the knocked out of AhR using CRISPR/Cas9, resulting significantly decreased expression of 7.69-fold for AhR and 3.70-fold for Cyp1B1 in the cells. These cell clones and CRISPR/Cas9 vectors could be used as tools to investigate the functions of AhR in both AD-MSCs and other cell types.